A medical diamond-like film and preparation method thereof

By using a multi-layer film structure of metal base layer and periodic gradient layer combined with a titanium-doped diamond-like layer in diamond-like film, the problem of insufficient binding strength and hydrophobic performance of diamond-like films in the field of biomedical science is solved, and the further development is achieved. High hardness, wear resistance and biocompatibility to meet the performance needs of medical devices.

CN116121705BActive Publication Date: 2024-12-31ZHONGKE MICROCRYSTALLINE MEDICAL TECH (SUZHOU) CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310176954.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-28
Publication Date
2024-12-31
Estimated Expiration
2043-02-28

AI Technical Summary

Technical Problem

Diamond-like films have problems such as poor binding strength and insufficient hydrophobic properties in the application of biomedical fields. The existing doped metal methods lead to decline in mechanical properties and stress corrosion, making it difficult to meet the needs of the third type of medical devices.

Method used

A multi-layer film structure with metal base layer/periodic gradient layer/titanium-doped diamond layer is adopted. The periodic gradient layer is formed by alternately deposition of TiCrN and TiSiCN layers to achieve a slow transition of components and structures, reduce internal stress, and enhance bonding strength. , hardness, wear resistance and hydrophobicity.

Benefits of technology

It significantly improves the overall performance of diamond-like films, meets the demand for material performance of medical devices, enhances biocompatibility and friction-reducing lubrication performance, avoids structural defects and cracks, and improves wear resistance, hardness and oxidation resistance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention belongs to the technical field of thin film materials, and specifically discloses a medical diamond-like film and a preparation method thereof. The medical diamond-like film comprises: a metal base layer deposited on a substrate; a periodic gradient layer deposited on the base layer; a titanium-doped diamond-like layer deposited on the periodic gradient layer; wherein the periodic gradient layer is a multi-periodic film layer formed by alternating deposition of TiCrN layer and TiSiCN layer. The present invention achieves a slow transition of composition and structure by adopting a multilayer film structure of a metal base layer / periodic gradient layer / titanium-doped diamond-like layer, greatly reduces the internal stress of the film layer, and effectively improves the overall comprehensive properties of the film layer, such as bonding strength, hardness, wear resistance, toughness and hydrophobicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thin film materials, and particularly relates to a medical diamond-like film and a preparation method thereof. Background Art

[0002] Diamond-like Carbon (DLC) is a type of sp 3 Hybridized carbon atoms and sp in graphite structure 2 Metastable amorphous materials composed of hybrid carbon atoms are gradually gaining attention as new materials in the biomedical industry due to their good biocompatibility, high hardness, low friction coefficient and low thermal expansion coefficient. At present, some studies have tried to use diamond-like films as biological coatings, such as surface coatings for medical devices or implant materials to improve their wear resistance and surface activity.

[0003] However, due to the residual stress in the diamond-like film itself, and the physical properties (such as thermal expansion coefficient) and mechanical properties (hardness, modulus) of the substrate, the bonding strength between the diamond-like film and the substrate is poor, and it is easy to delaminate, peel off and fail. In addition, the hydrophobicity of the diamond-like film is poor, and the contact angle is mostly around 60°, which cannot effectively prevent blood and cell adhesion. In the prior art, a hydrogen-containing multilayer diamond-like film doped with metal is prepared to reduce the residual stress, thereby increasing the film-base bonding force. However, the doped metal will cause the mechanical properties of the film to decrease, thereby inducing stress corrosion, and still cannot meet the hydrophobicity requirements of Class III medical devices. Therefore, how to further effectively improve the bonding strength and hydrophobicity of the diamond-like film deposited on the surface of the titanium alloy substrate, while maintaining the excellent performance of the film, is a key problem that needs to be solved in the application of diamond-like films in the biomedical field. Summary of the invention

[0004] In view of this, an embodiment of the present invention provides a medical diamond-like film and a preparation method thereof. By adopting a multilayer film structure of a metal base layer / periodic gradient layer / titanium-doped diamond-like layer, a slow transition of composition and structure is achieved, the internal stress of the film layer is greatly reduced, and the overall comprehensive properties of the film layer, such as bonding strength, hardness, wear resistance, toughness and hydrophobicity, are effectively improved.

[0005] In order to achieve the above-mentioned object of the invention, the embodiment of the present invention adopts the following technical solution:

[0006] In a first aspect, an embodiment of the present invention provides a medical diamond-like film, comprising:

[0007] A metal primer layer deposited on a substrate;

[0008] a periodic gradient layer deposited on the metal primer layer;

[0009] A titanium-doped diamond-like carbon layer is deposited on the periodic gradient layer.

[0010] Among them, the periodic gradient layer is a multi-periodic film layer formed by alternating deposition of TiCrN layers and TiSiCN layers from bottom to top, the Cr content in each TiCrN layer decreases from the metal base layer to the titanium-doped diamond-like layer, and the Si content in each TiSiCN layer increases from the metal base layer to the titanium-doped diamond-like layer; the titanium-doped diamond-like layer contains hydrogen only on the surface.

[0011] The medical diamond-like film provided by the present invention has the following advantages over the prior art:

[0012] The present invention adopts the inventive concept of a gradual structure, introduces a metal base layer and a periodic gradient layer between the substrate and the diamond-like carbon layer, and obtains a multilayer film structure of metal base layer / periodic gradient layer / titanium-doped diamond-like carbon layer, thereby achieving a slow transition of composition and structure, greatly reducing the internal stress of the film layer, and effectively improving the overall bonding strength, hardness, wear resistance, toughness, hydrophobicity and other comprehensive properties of the film layer, which can meet the needs of medical devices for better material performance and has huge market potential and use value.

[0013] The present invention forms a periodic gradient layer by alternately depositing TiCrN layers and TiSiCN layers, and the Si and Cr contents present a gradient, so that the thermal expansion coefficients and mechanical properties of the substrate and the periodic gradient layer can be uniformly transitioned, and the bonding ability between the titanium-doped diamond-like carbon layer and the substrate can be further enhanced, and the atomic bonding mismatch caused by the large structural difference between adjacent materials during the deposition process can be avoided, resulting in a large number of structural defects such as voids, microcracks and lattice distortion; and the TiCrN layer and the TiSiCN layer can absorb strain energy, and the interface between the layers can effectively inhibit the movement of dislocations, prevent the generation and expansion of cracks, and achieve an ideal match between the hardness and toughness of the diamond-like film, and significantly improve the wear resistance, hardness, oxidation resistance and corrosion resistance of the material.

[0014] In addition, the side of the periodic gradient layer close to the metal base layer is a TiCrN layer, which has good affinity with the metal base layer and acts as a barrier layer for the diffusion of oxygen elements; the side close to the titanium-doped diamond-like carbon layer is a TiSiCN layer. The C element can further promote the titanium atoms in the titanium-doped diamond-like carbon layer to form a nanocrystalline or amorphous composite structure, and the Si element can combine with the diamond-like carbon film layer with Si-C bonds to improve SP 3The bond content is reduced, and the size of the graphite islands in the diamond-like film layer is reduced, the roughness and dynamic friction coefficient of the film layer surface are reduced, thereby reducing the internal stress of the entire film layer, improving the hardness and brittleness of the diamond-like film, and enhancing the mechanical strength and toughness of the diamond-like film.

[0015] The present invention provides a titanium-doped diamond-like carbon layer and introduces metal titanium to effectively improve the comprehensive properties of the film layer such as surface biocompatibility, hydrophobicity, friction and hardness, and some titanium atoms can bond with carbon atoms to generate TiC nanoparticles, which is beneficial to the graphitization of the diamond-like film, reduces the internal stress of the diamond-like film, and improves the wear resistance of the diamond-like film; at the same time, compared with the hydrogen-containing diamond-like film, the hydrogen-free diamond-like film has higher hardness, larger elastic modulus and better wear resistance. In the present invention, the titanium-doped diamond-like layer only contains hydrogen on the surface, and while ensuring high hardness, excellent wear resistance and corrosion resistance, the passivation behavior of the H element on the friction interface is used to improve the friction reduction and lubrication performance of the film layer, and effectively reduce the friction between the film and the human body tissue.

[0016] Optionally, the alternating deposition cycle is 10 to 20.

[0017] The preferred alternating deposition cycle makes the thickness of the prepared periodic gradient layer appropriate, which can effectively enhance the wear resistance, hardness and bonding strength of the film as a whole. If the film layer is too small, it is difficult to achieve the purpose of improving the wear resistance and hardness of the substrate surface. If the film layer is too large, the bonding ability between the diamond-like film and the substrate will be reduced, making the coating easier to peel off.

[0018] Optionally, the thickness of the TiCrN layer is 0.8 μm to 1.5 μm.

[0019] Optionally, the thickness of the TiSiCN layer is 0.5 μm to 1 μm.

[0020] The preferred TiSiCN layer thickness and TiCrN layer thickness have good lattice matching, which allows the cubic TiSiCN subphase to stably exist in the nano-multilayer film structure under the template effect of the face-centered cubic TiCrN layer, forming a coherent epitaxially grown polycrystalline superlattice, which has a strong inhibitory effect on dislocation movement and significantly improves the wear resistance and hardness of the film layer.

[0021] Optionally, the Si content in the periodic gradient layer is 5% to 18%.

[0022] Optionally, the Cr content in the periodic gradient layer is 10% to 30%.

[0023] Optionally, the H content on the surface of the titanium-doped diamond-like carbon layer is 5% to 24%.

[0024] Optionally, the Ti content of the titanium-doped diamond-like carbon layer is 2% to 30%.

[0025] Optionally, the Ti doping amount in the titanium-doped diamond-like carbon layer decreases gradually from the periodic gradient layer toward the surface of the titanium-doped diamond-like carbon layer.

[0026] The present invention optimizes the Ti content and sets the Ti doping amount to decrease from the inside to the outside, thereby effectively improving the bonding force between the entire film layer and the substrate and better improving the biocompatibility and hydrophobicity of the diamond-like carbon film layer.

[0027] Optionally, the thickness of the primer layer is 0.5 μm to 3 μm.

[0028] Optionally, the titanium-doped diamond-like carbon layer has a thickness of 2.5 μm to 7.5 μm.

[0029] Optionally, the material of the metal base layer is Cr or Ti.

[0030] Further optionally, the matrix material includes but is not limited to metal-based biomaterials, ceramic-based biomaterials or polymer-based biomaterials.

[0031] Further optionally, the metal-based biomaterial includes but is not limited to stainless steel, magnesium and its alloys.

[0032] Further optionally, the ceramic-based biomaterial includes but is not limited to TiO2 film, isotropic pyrolytic carbon, hydroxyapatite, diamond and diamond-like carbon.

[0033] Further optionally, the polymer-based biomaterial includes but is not limited to polyester, polytetrafluoroethylene, polyurethane, polyoxymethylene, silicone rubber, polylactic acid, glycolide-lactide copolymer, polytrimethylene carbonate and polycaprolactone.

[0034] In a second aspect, an embodiment of the present invention provides a method for preparing the above-mentioned medical diamond-like film, comprising the following steps:

[0035] The metal base layer, the periodic gradient layer and the titanium-doped hydrogen-free diamond-like layer are sequentially deposited on the substrate surface by magnetron sputtering, and then the surface of the titanium-doped hydrogen-free diamond-like layer is hydrogenated and modified to obtain a medical diamond-like film.

[0036] Optionally, the hydrogenation modification step includes: turning off the magnetron sputtering source, turning on the ion source, using H2 as the working gas source, performing surface hydrogenation modification on the titanium-doped hydrogen-free diamond-like layer, and controlling the hydrogen flow rate so that the surface of the titanium-doped hydrogen-free diamond-like layer obtains the required hydrogen content.

[0037] Optionally, the H2 flow rate in the hydrogenation modification treatment is 5 sccm to 30 sccm.

[0038] The optimal flow rate can achieve precise control of the H element content on the surface of the diamond-like carbon layer without damaging the intrinsic mechanical properties of the diamond-like carbon layer.

[0039] Further optionally, the method for preparing the medical diamond-like film also includes pre-treating the substrate. The present invention does not specifically limit the operation of the pre-treatment, and conventional methods in the field may be used, such as polishing, ultrasonic cleaning, ion cleaning, and plasma etching.

[0040] Further optionally, each film layer of the diamond-like film described in the present invention can also be prepared by other conventional methods, such as linear ion beam method, vacuum cathode arc method, plasma-assisted chemical vapor deposition method and high-pressure glow discharge chemical deposition method.

[0041] Further optionally, in the process of preparing the periodic gradient layer and the titanium-doped hydrogen-free diamond-like carbon layer, a sputtering power / current gradient mode is used to achieve a gradient of the element content in the film layer, and the gradient mode can be a gradient gradient or a linear gradient. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0043] Example 1

[0044] This embodiment provides a medical diamond-like film, comprising

[0045] A metal primer layer deposited on a substrate;

[0046] a periodic gradient layer deposited on the metal primer layer;

[0047] a titanium-doped diamond-like carbon layer deposited on the periodic gradient layer;

[0048] Wherein, the metal base layer is made of Ti and has a thickness of 2 μm;

[0049] The periodic gradient layer is a multi-periodic film layer formed by alternating deposition of TiCrN layer and TiSiCN layer from bottom to top, a layer close to the metal base layer is a TiCrN layer, the Cr content in each TiCrN layer decreases from the metal base layer to the titanium-doped diamond-like layer, and the Si content in each TiSiCN layer increases from the metal base layer to the titanium-doped diamond-like layer, the alternating period is 15, the thickness of the TiCrN layer is 1.1 μm, the thickness of the TiSiCN layer is 0.8 μm, the Cr content in each TiCrN layer is 10% to 30%, and the Si content in each TiSiCN layer is 5% to 18%;

[0050] The titanium-doped diamond-like layer contains hydrogen only on its surface and has a thickness of 4.5 μm. The Ti doping amount decreases from the periodic gradient layer toward the surface of the titanium-doped diamond-like layer, the Ti content is 1.5% to 30%, and the surface H content is 20%.

[0051] The method for preparing the medical diamond-like carbon film comprises the following steps:

[0052] S1. Polish and ultrasonically clean the substrate in sequence, and then place it in the chamber of the magnetron sputtering equipment. First, vacuumize it to a vacuum degree of 3.0×10 -3 Pa, introduce argon with a flow rate of 20sccm, turn on the microwave source, and when the power reaches 850W, add a negative bias of 400V to the substrate stage and introduce cooling water, so that the argon ions sputter and clean the substrate for 10 minutes under the action of the negative bias.

[0053] S2. Magnetron sputtering coating is performed on the substrate surface with a Ti target as the target material, the Ti target power is controlled to be 300 W, the Ar flow rate is 30 sccm, and the substrate negative bias voltage is 200 V to obtain a metal base layer.

[0054] S3. Magnetron sputtering coating is carried out on the surface of the metal base layer with TiCr composite target and TiSiC composite target as target materials. By rotating the substrate holder, the substrate is reactively sputtered facing the TiSiC target and the TiCr target in turn. The Ar gas flow rate is controlled to be 40sccm, the N2 gas flow rate is 10sccm, the total gas pressure is 0.4Pa, the negative bias voltage of the substrate is 200V, and the sputtering power gradient gradual change mode is adopted. The power of the TiSiC target is increased from 150W to 300W, and the power of the TiCr target is reduced from 300W to 150W, so as to obtain a periodic gradient layer.

[0055] S4. Magnetron sputtering coating was performed on the surface of the periodic gradient layer using a TiC composite target as the target material. The Ar flow rate was controlled to be 15 sccm, the total gas pressure was 0.4 Pa, the sputtering power was linearly decreased from 200 W to 50 W, the substrate negative bias voltage was 250 V, and a titanium-doped hydrogen-free diamond-like carbon layer was obtained.

[0056] S5. Perform hydrogenation treatment on the surface of the titanium-doped hydrogen-free diamond-like layer. First, turn off the magnetron sputtering source, turn on the ion source, introduce H2 as the working gas source, control the gas flow rate to 20sccm, the ion source working current to 0.2A, the working power to 250W, and the substrate negative bias voltage to 50V to obtain a titanium-doped diamond-like layer, thereby completing the preparation of a medical diamond-like film.

[0057] The hardness, elastic modulus and friction coefficient of the obtained medical diamond-like carbon film were tested using a nanoindenter and a friction and wear tester. The experimental load was 10mN and the maximum load holding time was 5s. The results were: hardness was 37.1GPa, elastic modulus was 232GPa, and friction coefficient was 0.24.

[0058] The bonding strength of the obtained medical diamond-like carbon film was tested with a load of 5N. The overall observation showed that there were almost no cracks and no film peeling.

[0059] Example 2

[0060] This embodiment provides a medical diamond-like film, comprising

[0061] A metal primer layer deposited on a substrate;

[0062] a periodic gradient layer deposited on the metal primer layer;

[0063] a titanium-doped diamond-like carbon layer deposited on the periodic gradient layer;

[0064] Wherein, the metal base layer is made of Cr and has a thickness of 0.5 μm;

[0065] The periodic gradient layer is a multi-periodic film layer formed by alternating deposition of TiCrN layer and TiSiCN layer from bottom to top, a layer close to the metal base layer is a TiCrN layer, the Cr content in each TiCrN layer decreases from the metal base layer to the titanium-doped diamond-like layer, and the Si content in each TiSiCN layer increases from the metal base layer to the titanium-doped diamond-like layer, the alternating period is 10, the thickness of the TiCrN layer is 0.8 μm, the thickness of the TiSiCN layer is 0.5 μm, the Cr content in each TiCrN layer is 10% to 15%, and the Si content in each TiSiCN layer is 5% to 10%;

[0066] The titanium-doped diamond-like layer contains hydrogen only on its surface and has a thickness of 2.5 μm. The Ti doping amount decreases from the periodic gradient layer toward the surface of the titanium-doped diamond-like layer, the Ti content is 1.5% to 5%, and the surface H content is 5%.

[0067] The method for preparing the medical diamond-like carbon film comprises the following steps:

[0068] S1. Polish and ultrasonically clean the substrate in sequence, and then place it in the chamber of the magnetron sputtering equipment. First, vacuumize it to a vacuum degree of 3.0×10 -3 Pa, introduce argon with a flow rate of 20sccm, turn on the microwave source, and when the power reaches 850W, add a negative bias of 400V to the substrate stage and introduce cooling water, so that the argon ions sputter and clean the substrate for 10 minutes under the action of the negative bias.

[0069] S2. Magnetron sputtering coating is performed on the substrate surface with a Cr target as the target material, the Ti target power is controlled to be 300 W, the Ar flow rate is 30 sccm, and the substrate negative bias voltage is 200 V to obtain a metal base layer.

[0070] S3. Magnetron sputtering coating is carried out on the surface of the metal base layer with TiCr composite target and TiSiC composite target as target materials. By rotating the substrate holder, the substrate is reactively sputtered facing the TiSiC target and the TiCr target in turn. The Ar gas flow rate is controlled to be 40sccm, the N2 gas flow rate is 10sccm, the total gas pressure is 0.4Pa, the negative bias voltage of the substrate is 200V, and the sputtering power gradient gradual change mode is adopted. The power of the TiSiC target is increased from 150W to 300W, and the power of the TiCr target is reduced from 300W to 150W, so as to obtain a periodic gradient layer.

[0071] S4. Magnetron sputtering coating was performed on the surface of the periodic gradient layer using a TiC composite target as the target material. The Ar flow rate was controlled to be 15 sccm, the total gas pressure was 0.4 Pa, the sputtering power was linearly decreased from 200 W to 50 W, the substrate negative bias voltage was 250 V, and a titanium-doped hydrogen-free diamond-like carbon layer was obtained.

[0072] S5. Perform hydrogenation treatment on the surface of the titanium-doped hydrogen-free diamond-like carbon layer. First, turn off the magnetron sputtering source, turn on the ion source, introduce H2 as the working gas source, control the gas flow rate to 5sccm, the ion source working current to 0.2A, the working power to 250W, and the substrate negative bias voltage to 50V to obtain a titanium-doped diamond-like carbon layer, thereby completing the preparation of a medical diamond-like film.

[0073] The hardness, elastic modulus and friction coefficient of the obtained medical diamond-like carbon film were tested using a nanoindenter and a friction and wear tester. The experimental load was 10 mN and the maximum load holding time was 5 s. The results were: hardness was 36.4 GPa, elastic modulus was 221 GPa, and friction coefficient was 0.27.

[0074] The bonding strength of the obtained medical diamond-like carbon film was tested with a load of 5N. The overall observation showed that there were almost no cracks and no film peeling.

[0075] Example 3

[0076] This embodiment provides a medical diamond-like film, comprising

[0077] A metal primer layer deposited on a substrate;

[0078] a periodic gradient layer deposited on the metal primer layer;

[0079] a titanium-doped diamond-like carbon layer deposited on the periodic gradient layer;

[0080] Wherein, the metal base layer is made of Cr and has a thickness of 3 μm;

[0081] The periodic gradient layer is a multi-periodic film layer formed by alternating deposition of TiCrN layer and TiSiCN layer from bottom to top, a layer close to the metal base layer is a TiCrN layer, the Cr content in each TiCrN layer decreases from the metal base layer to the titanium-doped diamond-like layer, and the Si content in each TiSiCN layer increases from the metal base layer to the titanium-doped diamond-like layer, the alternating period is 20, the thickness of the TiCrN layer is 1.5 μm, the thickness of the TiSiCN layer in each TiCrN layer is 1 μm, the Cr content in each TiCrN layer is 25% to 30%, and the Si content in each TiSiCN layer is 14% to 18%;

[0082] The titanium-doped diamond-like layer contains hydrogen only on its surface and has a thickness of 7.5 μm. The Ti doping amount decreases from the periodic gradient layer toward the surface of the titanium-doped diamond-like layer, the Ti content is 20% to 30%, and the surface H content is 24%.

[0083] The method for preparing the medical diamond-like carbon film comprises the following steps:

[0084] S1. Polish and ultrasonically clean the substrate in sequence, and then place it in the chamber of the magnetron sputtering equipment. First, vacuumize it to a vacuum degree of 3.0×10 -3 Pa, introduce argon with a flow rate of 20sccm, turn on the microwave source, and when the power reaches 850W, add a negative bias of 400V to the substrate stage and introduce cooling water, so that the argon ions sputter and clean the substrate for 10 minutes under the action of the negative bias.

[0085] S2. Magnetron sputtering coating is performed on the substrate surface with a Ti target as the target material, the Ti target power is controlled to be 300 W, the Ar flow rate is 30 sccm, and the substrate negative bias voltage is 200 V to obtain a metal base layer.

[0086] S3. Magnetron sputtering coating is carried out on the surface of the metal base layer with TiCr composite target and TiSiC composite target as target materials. By rotating the substrate holder, the substrate is reactively sputtered facing the TiSiC target and the TiCr target in turn. The Ar gas flow rate is controlled to be 40sccm, the N2 gas flow rate is 10sccm, the total gas pressure is 0.4Pa, the negative bias voltage of the substrate is 200V, and the sputtering power gradient gradual change mode is adopted. The power of the TiSiC target is increased from 150W to 300W, and the power of the TiCr target is reduced from 300W to 150W, so as to obtain a periodic gradient layer.

[0087] S4. Magnetron sputtering coating was performed on the surface of the periodic gradient layer using a TiC composite target as the target material. The Ar flow rate was controlled to be 15 sccm, the total gas pressure was 0.4 Pa, the sputtering power was linearly decreased from 200 W to 50 W, the substrate negative bias voltage was 250 V, and a titanium-doped hydrogen-free diamond-like carbon layer was obtained.

[0088] S5. Perform hydrogenation treatment on the surface of the titanium-doped hydrogen-free diamond-like carbon layer. First, turn off the magnetron sputtering source, turn on the ion source, introduce H2 as the working gas source, control the gas flow rate to 30sccm, the ion source working current to 0.2A, the working power to 250W, and the substrate negative bias voltage to 50V to obtain a titanium-doped diamond-like carbon layer, thereby completing the preparation of a medical diamond-like film.

[0089] The hardness, elastic modulus and friction coefficient of the obtained medical diamond-like carbon film were tested using a nanoindenter and a friction and wear tester. The experimental load was 10 mN and the maximum load holding time was 5 s. The results were: hardness was 37.8 GPa, elastic modulus was 230 GPa, and friction coefficient was 0.25.

[0090] The bonding strength of the obtained medical diamond-like carbon film was tested with a load of 5N. The overall observation showed that there were almost no cracks and no film peeling.

[0091] Comparative Example 1

[0092] This comparative example provides a medical diamond-like carbon film, which differs from Example 1 in that a TiSiCN gradient layer of equal thickness is used to replace the periodic gradient layer, and the Si content is 5% to 18%.

[0093] The process adjustment of step S3 is as follows: magnetron sputtering coating is performed on the surface of the metal base layer with a TiSiC composite target as the target material, the Ar gas flow rate is controlled to be 40 sccm, the N2 gas flow rate is 10 sccm, the total gas pressure is 0.4 Pa, the substrate negative bias voltage is 200 V, and the sputtering power gradient gradual change mode is adopted. The TiSiC target power is increased from 150 W to 300 W to obtain a TiSiCN gradient layer.

[0094] The hardness, elastic modulus and friction coefficient of the obtained medical diamond-like carbon film were tested by nanoindenter and friction and wear tester. The experimental load was 10mN and the maximum load holding time was 5s. The results were: hardness was 24.1GPa, elastic modulus was 145GPa, and friction coefficient was 0.45;

[0095] The bonding strength of the obtained medical diamond-like carbon film was tested with a load of 5N. The overall observation showed that there were some micro cracks and film peeling.

[0096] Comparative Example 2

[0097] This comparative example provides a medical diamond-like carbon film, which is different from Example 1 in that the Cr content in each TiCrN layer is 30%.

[0098] The process adjustment of step S3 is as follows: magnetron sputtering coating is performed on the surface of the metal base layer with TiCr composite target and TiSiC composite target as target materials, and the substrate is reactively sputtered facing the TiSiC target and the TiCr target in turn by rotating the substrate holder, and the Ar gas flow rate is controlled to be 40sccm, the N2 gas flow rate is 10sccm, the total gas pressure is 0.4Pa, the negative bias voltage of the substrate is 200V, and the sputtering power gradient gradual change mode is adopted. The power of the TiSiC target is increased from 150W to 300W, while the power of the TiCr target is kept unchanged at 300W to obtain a periodic gradient layer.

[0099] The hardness, elastic modulus and friction coefficient of the obtained medical diamond-like carbon film were tested using a nanoindenter and a friction and wear tester. The experimental load was 10 mN and the maximum load holding time was 5 s. The results were: hardness was 20.5 GPa, elastic modulus was 114 GPa, and friction coefficient was 0.49.

[0100] The bonding strength of the obtained medical diamond-like carbon film was tested with a load of 5N. The overall observation showed that there were some micro cracks and film peeling.

[0101] Comparative Example 3

[0102] This comparative example provides a medical diamond-like film, which is different from Example 1 in that the titanium-doped diamond-like layer is a hydrogen-free diamond-like layer, and the process of step S4 is adjusted to complete the preparation of the medical diamond-like film after obtaining the titanium-doped hydrogen-free diamond-like layer.

[0103] The hardness, elastic modulus and friction coefficient of the obtained medical diamond-like carbon film were tested using a nanoindenter and a friction and wear tester. The experimental load was 10mN and the maximum load holding time was 5s. The results were: hardness was 27.3GPa, elastic modulus was 156GPa, and friction coefficient was 0.62.

[0104] The bonding strength of the obtained medical diamond-like carbon film was tested with a load of 5N. The overall observation showed that there were some micro cracks and film peeling.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A medical diamond-like carbon film, characterized in that: The medical diamond-like film consists of the following structure: A metal primer layer deposited on a substrate; a periodic gradient layer deposited on the metal primer layer; a titanium-doped diamond-like carbon layer deposited on the periodic gradient layer; The periodic gradient layer is a multi-periodic film layer formed by alternating deposition of TiCrN layer and TiSiCN layer from bottom to top, the Cr content in each TiCrN layer decreases from the metal base layer to the titanium-doped diamond-like layer, and the Si content in each TiSiCN layer increases from the metal base layer to the titanium-doped diamond-like layer; the period of alternating deposition is 10 to 20; the thickness of the TiCrN layer is 0.8 μm to 1.5 μm; the thickness of the TiSiCN layer is 0.5 μm to 1 μm; the titanium-doped diamond-like layer only contains hydrogen on the surface; the Ti doping amount in the titanium-doped diamond-like layer decreases from the periodic gradient layer to the surface of the titanium-doped diamond-like layer; the Si content in each TiSiCN layer is 5%~18%, the Cr content in each TiCrN layer is 10%~30%, the Ti content in the titanium-doped diamond-like layer is 1.5%~30%, the H content on the surface of the titanium-doped diamond-like layer is 5%~24%, and the thickness of the titanium-doped diamond-like layer is 2.5μm~7.5μm.

2. The medical diamond-like film according to claim 1, characterized in that: The thickness of the primer layer is 0.5 μm to 3 μm.

3. The medical diamond-like film according to claim 1, characterized in that: The material of the metal primer layer is Cr or Ti.

4. A method for preparing a medical diamond-like film according to any one of claims 1 to 3, characterized in that: The steps include: The metal base layer, the periodic gradient layer and the titanium-doped hydrogen-free diamond-like layer are sequentially deposited on the substrate surface by magnetron sputtering, and then the surface of the titanium-doped hydrogen-free diamond-like layer is hydrogenated to obtain a medical diamond-like film.

5. The method for preparing a medical diamond-like film according to claim 4, characterized in that: The hydrogenation modification treatment step includes: turning off the magnetron sputtering source, turning on the ion source, using H2 as the working gas source, and performing surface hydrogenation modification on the titanium-doped hydrogen-free diamond-like carbon layer.

6. The method for preparing a medical diamond-like film according to claim 5, characterized in that: The H2 flow rate in the hydrogenation modification treatment is 5 sccm~30 sccm.

Citation Information

Patent Citations

  • Superlubricity multilayer nano composite coating and preparation method thereof

    CN104846332A

  • Low friction coatings with improved abrasion and wear properties and methods of making

    CN104870692A

  • Ultralow-friction solid-liquid composite lubricating coating and preparation method thereof

    CN114196913A

  • Biomedical composite coating and preparation method thereof

    CN114959585A

  • Surface-coated cutting tool

    JP2009034781A